Horsefly dress : poems - Cahoon, Heather (Heather M.) (Sun tracks ;, 2020)
"Horsefly Dress, named after the only daughter of Coyote, a prominent and important figure in Salish oral traditions, deals with issues stemming from Coyote's transformation of the world and his decision to leave present certain various evils, including cruelty, greed, hunger, and death. These topics are explored through first-person accounts and the experiences of the author's family and tribal community. The poems throughout vary in style, each contributing to a larger narrative. Readers first encounter Coyote, learning more about his daughter and her significance to the speaker. Brutal truths about the lives of indigenous women are then revealed through poignant imagery such as Horsefly Dress holding the speaker's nephew on the opposite side of the river of death. As we go, we discover the ways in which the past and future are blurred, and how memories and dreams are the most significant markers of the speaker's life. By the end of the collection, we have become witnesses to a non-linear pattern of events, reminding us that we are all connected, and we cannot let who we are, our specific cultures and histories, to be erased"--